The transformation of a frontier: State and regional relationships in Panama, 1972-1990 (2022)
eng: This article examines changing political and social relationships at local, national, and international levels, over an 18-year period during and after the construction of a hydroelectric dam project in eastern Panama. A central point is that the state should not be viewed as a monolithic entity as it formulates and implements policy. Rather, conflicts of interest exist among different officials and agencies within the government, leading to vacillation in policy and outcome. In Panama, that conflict was influenced by international events and ties between the country and multilateral institutions. After the dam was built, Panama's Bayano region went from a frontier to a zone closely linked to the metropolis by economic and political ties, with disastrous consequences for the ecology and for the poor. This decline resulted despite efforts on the part of some state officials to protect its ecology through implementation of a sustainable development plan. The reasons why the sustainable development alternative failed and the consequences of this failure for indigenous people and poor small-holder colonists are also documented.